Science and Innovation Policy in France - Pierre-Bruno Ruffini (Foresight and STI Governance, 2008)
The paper presents the current state of research and innovation in France, describes the approaches to S&T policy, analyses tools for support of innovation and technological development. There are continuing problems of interaction between universities and research institutions in France that are essential for the country’s system of science, as well as the lack of research in the business sector.